Analisis dan Perancangan Aplikasi Basis Data Penilaian Kinerja Karyawan menggunakan Metode 360-Degree Feedback Berbasis Web pada Pt Ifs Solutions Indonesia - Choirul Huda; Andika Gilang Nugraha; Alwin Ghifari; Axel Didha Dewangga (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The purpose of this study is to analyze and design a database application for the assessment of employee performance to suit the needs of PT IFS Solutions Indonesia. This system creates and provides information quickly and accurately where the data is well integrated, so it can help the company to do an analysis and consideration for decision-making. The research methodology used includes library research, interviews with the HR company to obtain information about the system to be designed, and database design by creating conceptual models, logical models and physical models. After that, application design includes designing the DFD, menu structure, STD, and user interface. The result achieved is the creation of a web-based database application that can help decision-makers to support employees with good, more accurate, easier and quickly available when needed. The database application made can help companies manage and make decisions as well as produce better work.